Dynamic Panel Analysis of the Effect of FDI, Domestic Investment, and Remittances on Per Capita Income in Indonesia - Eka Agustiani; Endang Astuti (Indonesian Journal of Business Analytics, 2026)
This study analyzes the effect of Foreign Direct Investment (FDI), Domestic Investment (DI), and remittances on per capita income in Indonesia using a dynamic panel data approach. The study employs balanced panel data covering 38 provinces in Indonesia during the 2013–2023 period, with a total of 418 observations obtained from the Central Statistics Agency (BPS). The estimation method used is the Difference GMM Arellano-Bond to address endogeneity issues and dynamic bias caused by the presence of a lagged dependent variable. The validity of the model is confirmed through the Sargan test (prob = 0.3082) and the AR(2) test (prob = 0.2840), both of which satisfy the required criteria. The estimation results indicate that FDI, DI, and remittances all have a positive and significant effect on per capita income at the 99% confidence level. Remittances are the variable with the greatest influence (β = 0.2314), followed by FDI (β = 0.1128) and DI (β = 0.0654). Furthermore, evidence of income convergence among provinces is found, as indicated by the negative coefficient of the lagged per capita income variable (-0.1076), with an adjustment speed of 10.76% per year toward long-run equilibrium. The discussion is substantiated by empirical evidence from multiple Sinta 2 and 3 accredited studies, confirming the transmission mechanisms of FDI through technology spillovers and employment creation, the role of domestic investment in driving local economic activity, and the contribution of remittances through consumption and productive investment channels. This study recommends strengthening the investment climate, equalizing the distribution of domestic investment beyond Java, and channeling remittances toward productive activities as strategies for achieving inclusive and sustainable improvements in welfare across all regions of Indonesia.